PPAR gamma 2 prevents lipotoxicity by controlling adipose tissue expandability and peripheral lipid metabolism. - Medina-Gomez, G; Gray, S; Yetukuri, L; Shimomura, K; Virtue, S; Campbell, M; Curtis, R; Jimenez-Linan, M; Blount, M; Yeo, G; Lopez, M; Seppanen-Laakso, T; et al. (Public Library of Science, 2007)
Peroxisome proliferator activated receptor gamma 2 (PPARg2) is the nutritionally regulated isoform of PPARg. Ablation of PPARg2 in the ob/ob background, PPARg2-/- Lepob/Lepob (POKO mouse), resulted in decreased fat mass, severe insulin resistance, beta-cell failure, and dyslipidaemia. Our results indicate that the PPARg2 isoform plays an important role, mediating adipose tissue expansion in response to positive energy balance. Lipidomic analyses suggest that PPARg2 plays an important antilipotoxic role when induced ectopically in liver and muscle by facilitating deposition of fat as relatively harmless triacylglycerol species and thus preventing accumulation of reactive lipid species. Our data also indicate that PPARg2 may be required for the beta-cell hypertrophic adaptive response to insulin resistance. In summary, the PPARg2 isoform prevents lipotoxicity by (a) promoting adipose tissue expansion, (b) increasing the lipid-buffering capacity of peripheral organs, and (c) facilitating the adaptive proliferative response of beta-cells to insulin resistance.